Are Psychopathic Traits Associated with Core Social Networks? An Exploratory Study in University Students. (December 2020) - Reale, Kylie S.; Bouchard, Martin; Lim, Yan L.; Cook, Alana N.; Hart, Stephen D.
In a sample of 480 university students, we examined associations between self-ratings of psychopathic traits, made using the Comprehensive Assessment of Psychopathic Personality (CAPP), the Psychopathic Personality Inventory: Short Form (PPI: SF), and self-ratings of the structure of their core social networks (i.e., best friends, intimates). Results indicated that higher self-ratings of domains (CAPP) and subscales (PPI: SF) related to interpersonal dominance, manipulation, poor attachment, and emotional regulation were associated with less connected core networks. We interpret the dominance and manipulation domain and subscale findings as preliminary evidence of a deliberate strategy to provide a more influential position within one's social network. As for the associations with the attachment and emotional regulation domain and subscale findings, we suggest this could be reflective of deficits or a lack of desire both in establishing and maintaining long-term relationships.